Sistema de gestión de responsabilidad social universitaria: reflexiones en el contexto de la educación superior en Boyacá. (2020)
The purpose of this article is to present a proposal for a management system of University Social Responsibility, for which it was raised as a guiding question What actions of a University Social Responsibility System would be advanced in the context of higher education in Boyacá’s department? The methodology corresponds to a type of documentary research with a qualitative approach. The importance of the implementation of the management system is evident given the impact of training activities on the transformation of societies. In this sense as a relevant finding is the fact that while it is true there are substantial functions that fall within the scope of higher education institutions, from there is their social commitment, for this reason, dynamics must be generated where promote awareness scenarios for the different actors who are immersed in these training spaces in higher education.